Media and its role in the process of socialization in light of globalization - BOURGUIBA, Daoued (Social Sciences Journal)
Our study aims to search for the role of the media in the process of socialization through the factor of globalization, where it was affected by the modern information revolutions, so that societies lose their privacy little by little in the process of melting into the culture of the other, threatening the political entities of the less developed societies, which makes those societies merge into a global society In it, the weak and the owner of the corner of knowledge dominate the behaviors and capabilities of the knowledge seeker.